2003
DOI: 10.1016/s0163-6383(03)00033-x
|View full text |Cite
|
Sign up to set email alerts
|

The relation of flexible child care to quality of center day care and children’s socio-emotional functioning: A survey and observational study

Abstract: In two studies in daycare centers, we investigated a newly developed index for flexible child care describing parents' use of evening care and flexible attendance scheduling for their child. We examined the relation between this index together with stability in care, mother's stress and the child's temperament on the one hand, and quality of caregivers' behavior and a child's socio-emotional functioning in day care on the other. In Study I, the mothers and caregivers of 186 children (aged 6-30 months) particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 33 publications
5
63
2
1
Order By: Relevance
“…Another possible explanation could be the differences in types of care arrangements, or differences in the stability of the child care. Both aspects of child care have been associated with increased levels of behavior problems (Bacharach & Baumeister, 2003;De Schipper et al, 2003;Youngblade, 2003;). As shown in Table 1, both type and stability differed among the various quantity groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation could be the differences in types of care arrangements, or differences in the stability of the child care. Both aspects of child care have been associated with increased levels of behavior problems (Bacharach & Baumeister, 2003;De Schipper et al, 2003;Youngblade, 2003;). As shown in Table 1, both type and stability differed among the various quantity groups.…”
Section: Discussionmentioning
confidence: 99%
“…It appeared that the low quality had negative effects on the security attachment relations of the children. Several other studies cite the instability of child care and number of child care arrangements as risk factors for increased behavior problems (Bacharach & Baumeister, 2003;De Schipper et al, 2003;Youngblade, 2003). Thus, it seems that there is a relation between early child care and problem behaviors, but it remains unclear whether quantity of child care, quality, type, stability, or number of arrangements account for the findings.…”
Section: Recent Findings Of the National Institute Of Child Health Anmentioning
confidence: 99%
“…For children, however, day and night care may mean a less stable daily life. This notion is based on a study by De Schipper, Tavecchio, Van IJzendoorn and Linting (2003) on so called flexible child care, where flexible refers to families' schedules. In this study, more flexible child care was found to be associated with less daily stability in the structure of a child's program and his or her contacts with caregivers and peers.…”
Section: Day and Night Carementioning
confidence: 99%
“…In this study, more flexible child care was found to be associated with less daily stability in the structure of a child's program and his or her contacts with caregivers and peers. Furthermore, the daily stability of care mattered for the well-being of 6-to 39-month-old children in day care, as an increase in the variety and number of caregivers and peers was associated with less well-being (De Schipper et al, 2003). Although no direct association was found between flexible child care and child wellbeing, these results point to the potential challenge to young children's wellbeing posed by the varying and multiple social contacts characteristic of flexible child care arrangements.…”
Section: Day and Night Carementioning
confidence: 99%
“…교사가 훈육방식을 결정하는 과정에서 교사의 정서적․심 리적 특성 또한 매우 큰 작용을 하는 요소로 지목된다 (Scarr, 1988;Schipper et al, 2003). 기관 내에서 개인이 실제로 자신 이 느낀 정서를 외현적으로 나타낼 때는 적절한 정서적 표현 능력이 필요하다.…”
Section: 이와 같은 선행연구들의 결과는 교사의 훈육방식이 유아의 적 응과 관련이 있을 뿐만 아니라 초기 사회화 과정unclassified